2022
DOI: 10.3390/biom12070898
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neural Circuitry under General Anesthesia: New Methods and Findings

Abstract: General anesthesia has been widely utilized since the 1840s, but its underlying neural circuits remain to be completely understood. Since both general anesthesia and sleep are reversible losses of consciousness, studies on the neural-circuit mechanisms affected by general anesthesia have mainly focused on the neural nuclei or the pathways known to regulate sleep. Three advanced technologies commonly used in neuroscience, in vivo calcium imaging, chemogenetics, and optogenetics, are used to record and modulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…Since the loss of consciousness is a fundamental aspect shared by both sleep and general anesthesia, it has been proposed that these two states have overlapping neural endpoints. Research has demonstrated that the reversible loss and recovery of consciousness induced by anesthetics result from the precise regulation of various arousal or sleep nuclei [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the loss of consciousness is a fundamental aspect shared by both sleep and general anesthesia, it has been proposed that these two states have overlapping neural endpoints. Research has demonstrated that the reversible loss and recovery of consciousness induced by anesthetics result from the precise regulation of various arousal or sleep nuclei [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been successfully combined with behavioral paradigms in animals to investigate the role of speci c subtypes of neurons or their afferent/efferent circuits in various brain functions. For example, it has been used to study cognition-related neurons in the locus coeruleus nucleus [23] and depression responsive medium spiny neurons in the NAc [24]. Given the rapid transitions between anesthesia states, we utilized this technique to explore the downstream systems regulated by the PBN.…”
Section: Discussionmentioning
confidence: 99%
“…Optogenetics can precisely regulate the temporal accuracy of specific neurons or neural circuits ( Zhang et al, 2022 ). Opsins are usually introduced into neurons in the target region by injection of virus that contains the opsin gene, and experiments are performed approximately 3 weeks later.…”
Section: Optogeneticsmentioning
confidence: 99%
“…It is becoming increasingly evident that many of the neural circuits involved in the sleep–wake cycle are also relevant for general anesthesia. ( Zhang et al, 2022 ; Espinosa-Juárez et al, 2023 ). Studying neural networks necessitates the utilization of advanced techniques for neural labeling and modulation, including optogenetics, chemogenetics, electrophysiology, calcium imaging, anterograde/retrograde tracing behavioral testing, and so on.…”
Section: Introductionmentioning
confidence: 99%